Building Smart City Solutions with Focus on Health Care and GDPR - Enler, Emirhan; Pentek, Istvan; Adamko, Attila (Handbook of Smart Cities, 2021)
Novel solutions surrounding the Smart City Architectures derived from personal data have always been a challenging topic in recent decades. Both the volatility of the subject technologies implementing the architecture and the sensitivity of human-sourced data can be considered as the key contributors to these challenges. In this research, the goal was to identify antipatterns related to the possible architecture for a Smart City Solution by applying innovative software development methodologies and questioning proposed architecture’s efficacy in the fields of scalability, maintainability, autonomy, testability, and security via provisioning resolutions to the identified antipatterns. Research then focuses on applicable data management, sharing, and anonymization concepts that comply with the General Data Protection Regulation. The core concept of Data Protection allows the architecture to utilize a high-level abstraction business definition and extensibility. The envisioned characteristics of the aforementioned architecture solely rely on the disciplinary fields of Service Oriented Architecture and Component Oriented Development methodologies. This approach has been followed to issue a trend compatible solution which provides a well-defined foundation for advancements required by the evolving technology dependencies. After the architectural proposal, research carries on to the possible utilization of Smart City Solution as a Health Care service and consumption of the data that is provided by this service. The utilization gives an example of a healthcare workflow where the service abstraction plays a key role.